Vibration investigation of passenger car front suspension system under various road condition and driving maneuvers - Tanti Zanariah, Shamshir Ali (2010)
This thesis has the purpose to show the investigation of excitation and vehicle body movements acting on the two front wheel of the vehicle due to the road profile and driving maneuvers based on the experiments. This project endeavor to prove the effect road profile and speed on front suspension and car body movements based on centre of gravity can be used as representative conditions for ride comfort. It is believed that the front suspension is moving faster when the vehicle moves at high speed and due to the vehicle movements it shows that the road surface are irregularity. The procedures constructed on gaining the data on the front suspension linear motion and vehicle‟s centre of gravity performance in term of movement. Different kind of road surface irregularity has been considered and dissimilar driving maneuvers are identified. The study on the apparatus and instruments contributes in understanding the capabilities of its behavior on going experiments. The test is performed in Universiti Malaysia Pahang (UMP) and using UMP Test Car which has been installed with accelerometers and wire potentiometer sensor on the front suspension, Global Positioning System (GPS) and DEWESOFT software for data acquisition purpose. The analysis was performed using Flexpro 7. Based on the graphs and explanations, comparison between the road conditions due to the driving maneuvers and road variation are made. Thus this study results is comfort ride at all conditions of roads tested except bumpy road and the vehicle roll and yaw angle is high at roundabout road yet the pitch angle are increased at the bumpy road due to driving behavior. Based on the analysis it can be concluded that the front suspension and body of the vehicle are responsive towards the road profile and driving maneuvers. Consequently, this study contribute in identified the ride comfort on the track used for the optimization at other speeds. Lastly, this investigation that been justified in this thesis is only applicable for vehicle passenger.